Young students encyclopedia /cSpecially prepared with the staff of My weekly reader (American Education Publications, 1972)
Includes more than 2400 alphabetically arranged articles on general topics with an index and a glossary of terms
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries